Implementing a low‐starch biscuit‐free diet in zoo gorillas: The impact on health. Issue 1 (13th January 2014) - Less, E.H.; Lukas, K.E.; Bergl, R.; Ball, R.; Kuhar, C.W.; Lavin, S.R.; Raghanti, M.A.; Wensvoort, J.; Willis, M.A.; Dennis, P.M.
<x xml:space="preserve">Abstract</x> In the wild, western lowland gorillas consume a diet high in fiber and low in caloric density. In contrast, many gorillas in zoos consume a diet that is high‐calorie and low in fiber. Some items commonly used in captive gorilla diets contain high levels of starch and sugars, which are minimal in the natural diet of gorillas. There is a growing concern that captive gorillas may qualify as obese. Furthermore, the leading cause of death for adult male gorillas in zoos is heart disease. In humans, a diet that is high in simple carbohydrates is associated with both obesity and the incidence of heart disease. In response to these issues, we implemented a biscuit‐free diet (free of biscuits and low in fruit) and measured serum biomarkers of obesity and insulin resistance pre‐ and post‐diet change at three institutions: North Carolina Zoological Garden, Cleveland Metroparks Zoo, and Columbus Zoo and Aquarium. We also added a resistant starch supplement to gorilla diets at two of the above institutions. We anticipated that these diet changes would positively affect biomarkers of obesity and insulin resistance. Both diet manipulations led to a reduction in insulin. Resistant starch also decreased overall serum cholesterol levels. Future research will examine these health changes in a greater number of individuals to determine if the results remain consistent with these preliminary findings. Zoo Biol. 33:74–80, 2014. © 2014 Wiley Periodicals, Inc.